Symposium chronic pelvic pain: Introduction - Ascenzo Palacio, Alberto (2016)
Chronic pelvic pain (CPP) is that sensitive, subjective or emotional unpleasant experience, which is located at the lower abdomen, pelvis, lower back or hip that persists for more than six months and occurs continuously or intermittently, in women, not necessarily associated with the menstrual cycle (1).